ЗАДАЧА РОЗТАШУВАННЯ НАКОПИЧУВАЧІВ ЕЛЕКТРОЕНЕРГІЇ В ОЕС УКРАЇНИ З УРАХУВАННЯМ ЙОГО ВПЛИВУ НА ПОТОКИ ПОТУЖНОСТІ КОНТРОЛЬОВАНИМИ ПЕРЕТИНАМИ - Буткевич, О.Ф.; Юнєєва , Н.Т.; Гурєєва , Т.М.; Стецюк , П.І. (Інститут електродинаміки НАН України, Київ, 2020)
It is shown that when creating of electric energy storage system (EESS) in the Interconnected Power System (IPS) of Ukraine it is advisable to take into account the influence of the distribution (considering both location and power) of EESS batteries on the flows of active power transmitted by “problematic” controlled cutsets of the IPS of Ukraine. The method for solving the EESS distribution’s problem taking into account the specified influence is proposed. References 3, table 1.